2018
DOI: 10.3389/fnins.2018.00620
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex Activity Predicts Mental Fatigue in Young and Elderly Men During a 2 h “Go/NoGo” Task

Abstract: Background: Although the effects of mental fatigue on cognitive–motor function and psychological state in young adults are well-documented, its effects in the elderly are not completely understood. The aim of this study was to estimate the effect of prolonged cognitive load on the indicators of psychological, cognitive, and motor functions.Methods: Fifteen young and 15 elderly men were asked to perform a 2 h “Go/NoGo” task. Psychological state (mood and motivation), cognitive (prefrontal cortex activity and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Specifically, an increase in reaction time of 7% was found when comparing the data of the inhibitory stimuli pre- and post-Stroop task in the MF condition [ 20 ]; in comparison, the present study noted an increase of 9%. As the authors [ 20 ] mentioned, this is to be expected, as the effects of MF on cognitive performance are attributed to a decrease in executive control and attention, which makes it more difficult to deviate from automatic responses and focus on the task at hand [ 45 , 46 ]. This study, therefore, further adds to the theories of Baumeister et al [ 47 ], who suggested that prolonged mental demand exhausts self-control resources, which impairs executive functions, inhibiting specific processes and functional connectivity in the brain [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, an increase in reaction time of 7% was found when comparing the data of the inhibitory stimuli pre- and post-Stroop task in the MF condition [ 20 ]; in comparison, the present study noted an increase of 9%. As the authors [ 20 ] mentioned, this is to be expected, as the effects of MF on cognitive performance are attributed to a decrease in executive control and attention, which makes it more difficult to deviate from automatic responses and focus on the task at hand [ 45 , 46 ]. This study, therefore, further adds to the theories of Baumeister et al [ 47 ], who suggested that prolonged mental demand exhausts self-control resources, which impairs executive functions, inhibiting specific processes and functional connectivity in the brain [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies suggested a four-factor subscale factor analytic solution of the EI construct: perception of emotion, managing one’s own emotions, managing others’ emotions, and utilization of emotion (Ciarrochi, Chan, & Bajgar, 2001). Most recent studies in Lithuania, where the EI scale was applied, use four subscale analyses (Malinauskas, Dumciene, Sipaviciene, & Malinauskiene, 2018; Terentjeviene et al., 2018). In our study, we used total sum score of EI, and average scores for all four of these EI subscales.…”
Section: Methodsmentioning
confidence: 99%
“…Even when workers might not be subjectively experiencing fatigue, there is mounting evidence that decision fatigue begins to set in after several hours of sustained work [ 23 ]. Decision fatigue has been attributed to a decline in executive function, localized in the prefrontal cortex of the brain, likely associated with an increased use of heuristics, and a decline in quality of decision making [ 24 ]. In some of the cases reviewed here, fatigue was very evident, but in others decision fatigue may have influenced outcome in more subtle ways.…”
Section: Discussionmentioning
confidence: 99%